Food safety practices and its associated factors among food handlers in selected food establishments in Jigjiga Town, Somali Regional State, Eastern Ethiopia - Dek Kahin Yosef; Tewodros Tesfa; Getachew Kabew Mekonnen; Kassahun Bogale; Mohammed Ahmed (Discover Food)
Abstract Background Food hygiene is the primary public health concern for many countries, as contaminated food is a potential source of serious microbial infections, food poisoning, or economic loss due to spoilage. The aim of this study was to assess food safety practices and associated factors among food handlers in selected public food establishments in Jigjiga town. Methods An institution based cross-sectional study was conducted from August 28 to December 1 2023, using a systematic sampling technique, and data were collected using a structured questionnaire and observational checklist. Descriptive statistics, and binary and multivariable logistic regression models were employed. The p-value of < 0.05 with 95% confidence interval was used as a significant cut point. Result A total of 406 food handlers with a 100% response rate. Nearly, 63% (254) of participants were male. The findings of this study revealed that a considerable number, 138 (34.0%) of the respondents were found to have an unfavorable attitude towards food safety practices with a mean score of 46.26 (SD = 6.84), while 232 (57.1%) had good food safety practices. In the multivariable logistic analysis, variables such as sex, work experience, availability of a washing basin, cleaning utensils with hot water and soap, and others had a significant association with food safety practices observed among food handlers in Jigjiga town. Conclusion Many vital individual and institutional factors influencing the food safety practices of food establishments were identified. The food establishment owners, food handlers, and local health offices should work hard on food safety practices improvement.